2012
DOI: 10.1098/rsbl.2012.0282
|View full text |Cite
|
Sign up to set email alerts
|

Diversity–disturbance relationships: frequency and intensity interact

Abstract: An influential ecological theory, the intermediate disturbance hypothesis (IDH), predicts that intermediate levels of disturbance will maximize species diversity. Empirical studies, however, have described a wide variety of diversity-disturbance relationships (DDRs). Using experimental populations of microbes, we show that the form of the DDR depends on an interaction between disturbance frequency and intensity. We find that diversity shows a monotonically increasing, unimodal or flat relationship with disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 23 publications
8
70
1
2
Order By: Relevance
“…Prior work using a single-strain system ( Pseudomonas fluorescens ) showed that coexistence of colony morphotypes peaked at intermediate levels of disturbance and productivity (3335), but it is unclear whether these results translate to more complex communities. Recent laboratory work has shown that multispecies microbial community responses to disturbance depend not only on intensity but also on the frequency of disturbance application (34, 36), suggesting that a simple universal relationship between diversity and disturbance may not exist. We expanded on this prior work and developed an experimental system comprised of a complex bacterial community enriched from Lake Ontario, wherein we could precisely define the dimensions of disturbance (e.g., disturbance type, range, intensity, and frequency) and quantitatively sample community diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work using a single-strain system ( Pseudomonas fluorescens ) showed that coexistence of colony morphotypes peaked at intermediate levels of disturbance and productivity (3335), but it is unclear whether these results translate to more complex communities. Recent laboratory work has shown that multispecies microbial community responses to disturbance depend not only on intensity but also on the frequency of disturbance application (34, 36), suggesting that a simple universal relationship between diversity and disturbance may not exist. We expanded on this prior work and developed an experimental system comprised of a complex bacterial community enriched from Lake Ontario, wherein we could precisely define the dimensions of disturbance (e.g., disturbance type, range, intensity, and frequency) and quantitatively sample community diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The IDH is supported by studies of a variety of species and ecosystems (Flöder and Sommer, 1999;Molino and Sabatier, 2001;Roxburgh et al, 2004;Yuan et al, 2016), including a temperate grassland ecosystem (Yuan et al, 2016). However, numerous empirical studies have described a variety of diversitydisturbance relationships (MacKey and Currie, 2001;Cadotte, 2007;Randall Hughes et al, 2007;Hall et al, 2012). Some researchers believe that the IDH should be abandoned on empirical and theoretical grounds (Randall Hughes et al, 2007;Fox, 2013), whereas other researchers believe the data support the extension and refinement of the IDH (Randall Hughes et al, 2007) and suggest that the IDH forms the basis for the competition-colonization trade-off theory (Sheil and Burslem, 2013).…”
mentioning
confidence: 99%
“…(Danovaro & Fabiano 1995;James et al 2006) and it is plausible that the microbial community was impacted by the cold snap. Microbial diversity can increase following disturbance (Hall et al 2012a), and the community may have been in a period of recovery when we sampled it.…”
Section: Discussionmentioning
confidence: 99%